PRAWO DO OBRONY A DOWÓD Z ZEZNAŃ ŚWIADKA INCOGNITO W POLSKIM PROCESIE KARNYM - Wiliński, Paweł (Wydział Prawa i Administracji UAM, 2003)
The author describes the limits of the right to defence in the context of evidence by testimony of an anonymous witness. In practice, the introduction of the evidence by testimony of an anonymous witness to the Polish criminal system means that the legislator decides to limit the procedural rights of the defendant. The author notices the need to balance the defendant’s interest and right to defence against the witness’s right to personal security and the resulting prohibition of such execution of the right to defence that would lead to the violation of the fair interest of the other trial participants. Having analyzed the jurisprudence of the European Court of Human Rights the author comes to the conclusion that also in the light of the Court’s verdicts the introduction of an anonymous witness to the criminal procedure does not mean a breach of the right to defence. The author analyses some particular procedural rights of the defendant related to the evidence by testimony of an anonymous witness and shows to what degree these rights are modified in that situation. The author claims that whenever the threat to the witness’s life, freedom or health is more real and probable, greater limitations to the right to defence shall be accepted. Nevertheless, the procedure of examination of evidence should meet the standards following from procedural rules. The right to defence will be exercised in a way that does not breach the fairness of the trial if at least the following conditions are met: defendant and/or his counsel shall participate in the hearing of anonymous witness during the trial; defendant and/or his counsel shall be allowed to formulate questions to such a witness; they shall have the right to receive answers to the questions concerning the subject matter of the testimony, not the witness himself; questions not answered by the witness shall be included in the protocol of the trial and in its authenticated copy. The elementary principle to be observed is that, in every single situation, the parties have to compensate for all acceptable and admissible deviations from procedural rules and for the right to defence in particular. In such a situation, the compensation should broaden the rights of the defence and enable the exercise of those rights in practice.
THE RIGHT TO DEFENCE AND EVIDENCE BY TESTIMONY OF AN ANONYMOUS WITNESS